AKSESBILITAS BAGI DIFABEL PADA BANGUNAN MASJID - Awik Retyaka Afudaniati; Dwi Aries Himawanto (Universitas Mercu Buana, 2018)
Klaten is one of the cities that echo the city of inclusion. The city is still in the process of development in equipping accessible facilities and infrastructure for people with disabilities. Facilities in public buildings for disabled people have been built, although still not perfect. At the Al Aqsa Grand Mosque building Klaten facility has implemented building accessibility for the disabled. Therefore, to know the extent of the accessibility level of buildings for people with disabilities according to the standard needs of accessibility. For that researchers do location observation using measuring instruments, and cameras and conducted unstructured interviews on the board of the mosque. From this study that there is accessibility facility in Al Aqsa mosque building not yet accessible enough to be accessed by persons with disabilities because accessibility facility in Al Aqsa Grand Mosque building has not fulfill the proper design principles and Permen PU 30 / PRT / M / 2006.Keywords: accessibility, disabled, mosque